The pension system in Peru: Sustainability, coverage and replacement rate - Rodriguez Baca, Víctor Horacio (2025)
This article explores the challenges and possible solutions for Peru's pension system. After World War II and the ratification of the Universal Declaration of Human Rights in 1948, the right to social security was guaranteed. In Peru, the pension system has two regimes: the National Pension System (SNP) and the Private Pension System (SPP). However, it faces issues such as limited coverage (only 26.5% of the Economically Active Population is affiliated), a low replacement rate (27%), and financial sustainability problems due to high labor informality and the lack of diversification in the investments of Pension Fund Administrators (AFP). a qualitative approach has been applied. to identify the system's main limitations and suggests reforms that include improving coverage, increasing the replacement rate, and ensuring long-term financial sustainability. The study advocates for the implementation of incentives for affiliation, diversification of investments, and a review of the regulatory framework. Based on the experiences of countries like Norway and the Netherlands, the study calls for a mixed system that combines basic pensions with mandatory occupational schemes and voluntary savings to ensure a dignified and sustainable retirement.